2012
DOI: 10.24846/v21i3y201210
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Adaptive LQ Control of Nonlinear Process

Abstract: Abstract. The contribution is focused on the adaptive control of the nonlinear system represented by the continuous stirred-tank reactor with the spiral cooling in the jacket. The mathematical model of this reactor is described by two nonlinear ordinary differential equations which were solved numerically. The adaptive controller is based on the choice of the external linear delta model of the originally nonlinear process, parameters of which are identified recursively and parameters of the controller are reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…1DOF scheme is shown in Fig. 4 where Q(s) represents the transfer function of the controller in the feedback part and G(s) is ELM of the controlled system (8). Signal w is used for reference signal (wanted value), u is control input, y controlled output and e represents control error, e.g.…”
Section: Controller Designmentioning
confidence: 99%
See 2 more Smart Citations
“…1DOF scheme is shown in Fig. 4 where Q(s) represents the transfer function of the controller in the feedback part and G(s) is ELM of the controlled system (8). Signal w is used for reference signal (wanted value), u is control input, y controlled output and e represents control error, e.g.…”
Section: Controller Designmentioning
confidence: 99%
“…where α is position of the root which affects the quality of control and polynomial n(s) is obtained from the spectral factorization of the identified polynomial a(s) in the denominator of the ELM (8). The use of this factorization connects the design of the polynomial d(s) with the controlled system which helps with reduces generality of the Pole-placement method.…”
Section: Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiments (Vojtesek and Dostal 2012) have shown that it is good to connect the choice of the polynomial d(s) with the parameters of the controlled system, for example with the use of spectral factorization of the polynomial a(s) in the numerator of G(s) in (1) known from the recursive identification…”
Section: ( ) ( )mentioning
confidence: 99%
“…Because of the advantage of selfadaptation, adaptive controller can tolerate the uncertainties and external disturbances in closed-loop system [7,11,19,21]. In the adaptive control system, a common method for dealing with uncertainties including the parameters or structure is to design an adaptive parameter estimates algorithm or an auxiliary controller [3,4,14].…”
Section: Introductionmentioning
confidence: 99%